Delhi Weather Analysis : A Mongo Db Approach - Kazi, Aliya A; Shaikh, Shifa; Shaikh, Shahbaj; Shaikh, Shakila (International Journal of Computer Sciences and Engineering, 2019)
The application of science and technology in predicting the weather of a given area is weather forecasting. The whole world is experiencing extreme climatic change which causes side effects .In order to reduce these side effects we use mathematical algorithms and techniques on big data of weather data to analyse the current situation and predict the future weather conditions. In this research we will use be using Mongo DB to analyse the data on weather in Delhi. The outcomes shows us the analysis of the weather data available.